Efisiensi Penurunan Kandungan Uranium dalam Limbah Cair Pengolahan Monasit Menggunakan Resin Penukar Kation Tulsion T-40 Na - Walayudara, Inda Robayani; Laksmana, Roza Indra; Marisi, Dani Poltak; Amalia, Septyana Nur (BRIN Publishing, 2019)
Waste-water is one of the production process that contains several dangerous mixtures or chemical compositions. One of them is waste-water from monazite processing which is containing radioactive element like uranium (U). Waste-water with radioactive content, mainly uranium, became a hazardeous content if it is released to the environment because of its active nuclide content that effect the environment and community health. Therefore, it is necessary to treat waste-water from monasite processing. The method used is ion exchange process with a cation resin, namely Tulsion T-40 Na, which can reduce uranium content and other cations in waste-water at low concentration. Ion exchanging is conducted through stirring process with resin weight and contact time variations. Measurements on uranium content are carried out using the UV-Vis Spectrophotometer, while measurements on pH and TDS values in waste-water are conducted to determine the characteristics of the waste. The results showed that optimum condition of the ion exchange process at 1.5 g resin weight with 300 minutes contact time is resulting a reduction on uranium content as much as 83.40 %.